Caracterización productiva del período de postura, en gallinas Lohman, de la granja “El Roble” S.A.C.-Huanchaco - Zúñiga Ruíz, Zuleima (2019)
This research was carried out with the objective of characterizing the production of the laying period, in Lohman chickens, of the farm “El Roble” S.A.C, located in Huanchaco; also, calculate the level of egg production in Lhoman posture hens, up to the peak of production and determine poultry productivity in the field and period of study. Data from 6000 birds housed from the Lohman line were used, under a completely random design. Number of eggs, feed conversion, mortality, production percentage, data that were analyzed using Excel were evaluated. The results are as follows: 6.39 in numbers of eggs of the bird housed per week, 62.9 gr average weight of the egg, 0.13 feed conversion per egg, 2.13 conversion per egg mass, 1.8% average mortality percentage, 91.62% average of percentage of production. It is concluded that the posture period of the farm "El Roble" S.A.C is of optimum level and within the standard production parameters.